The molecular phenomena of the blaZ genes forming betalactamase enzymes structure in Staphylococcus aureus resistant to beta-lactam antibiotics (ampicillin) - Mieke Satari (Dental Journal (Majalah Kedokteran Gigi), 2010)
Background: Nowadays, infectious disease still an important problem. One of the bacteria causing infectious diseases is Staphylococcus aureus (S. aureus). In the effort to deal with infections caused by S. aureus, beta-lactam antibiotics, such as ampicillin, are used. In fact, it is unfortunately known that many of S. aureus bacteria are resistant to this group of antibiotics. Because of nucleotide base changes in the structure of the genes blaZ which encode beta-lactamase enzymes in S. aureus. Purpose: The objective of this study was to analyze the nucleotide base changes in the structure of the genes blaZ forming beta-lactamase enzymes in S. aureus resistant to ampicillin based on molecular point of view. Methods: Molecular examinations was conducted by isolating the genes, forming beta-lactamase enzyme, which length was 845bp, from 7 isolates of S. aureus resistant to ampicillin by using PCR technique. The results of blaZ amplification were then subjected to homology by using Tn 552 of S. aureus obtained from bank of genes. Results: Based on the result of the homology, it was found that there was a change in purine base TG, which was a pyrimidine base at the -37 position of the initial codon of blaZ. This change, however, did not affect the strength of the promoter since the number of A and T is still more than the number of G and C. In the structure of the blaZ gene there was even no mutation or deletion or nucleotide base substitution found, so it would not affect the effectiveness of beta-lactamase enzyme. Conclusion: It can be concluded that the resistance of S. aureus towards ampicillin was not caused by nucleotide base deletion/substation. It is suspected that there were other causes leading to the resistance, including the overproduction of beta-lactamase enzyme of the blaZ gene, causing the degradation of beta-lactam antibiotics.Latar belakang: Penyakit infeksi sampai saat ini masih merupakan masalah. Salah satu bakteri penyebab infeksi yaitu Staphylococcus aureus (S. aureus). Upaya menangani infeksi yang disebabkan S. aureus dapat menggunakan antibiotik golongan betalaktam, salah satunya ampisilin. Pada kenyataannya banyak S. aureus resisten terhadap antibiotik ini. Salah satu penyebab timbulnya resistensi ampisilin terhadap S. aureus yaitu adanya dugaan perubahan basa nukleotida dari gen struktur (blaZ) yang mengkode enzim betalaktamase. Tujuan: Untuk menganalisis perubahan basa nukleotida gen struktur pembentuk enzim betalaktamase pada S. aureus yang resisten ampisilin ditinjau secara molekuler. Metode: Pemeriksaan enzim betalaktamase secara molekuler dilakukan dengan mengisolasi gen pembentuk ensim betalaktamase (blaZ) yang memiliki panjang 845 pb terhadap 7 isolat S. aureus hasil isolasi yang berasal dari abses yang resisten terhadap ampisilin dengan mengunakan PCR . Hasil amplifikasi blaZ kemudian dilakukan homologi dengan Tn 552 S. aureus yang diperoleh dari bank gen. Hasil: Hasil homologi ditemukan adanya perubahan basa purin T  G yang merupakan basa pirimidin pada posisi –37 dari kodon awal blaZ. Perubahan ini tidak mempengaruhi kekuatan promoter karena jumlah A dan T masih lebih banyak dari G dan C. Pada gen struktur blaZ ini tidak terdapat adanya mutasi ataupun delesi maupun subsitusi basa nukleotida hingga tidak akan mempengaruhi efektifitas kerja enzim betalaktamase. Kesimpulan: Terjadinya resisten S. aureus terhadap ampisilin bukan disebabkan adanya mutasi maupun delesi/ subsitusi basa nukleotida dari blaZ namun diduga adanya sebab lain yaitu produksi berlebih enzim betalaktamase hingga semua antibiotik betalaktam akan didegradasi oleh enzim betalaktamase.